2018
DOI: 10.1186/s12879-018-3205-7
|View full text |Cite
|
Sign up to set email alerts
|

Bacille Calmette-Guérin (BCG) spondylitis with adjacent mycotic aortic aneurysm after intravesical BCG therapy: a case report and literature review

Abstract: BackgroundAlthough intravesical bacille Calmette-Guérin (BCG) therapy is accepted as an effective treatment for bladder cancer, serious complications may occur in rare cases. To date, only 4 cases have been reported in which the patient developed a combination of mycotic aortic aneurysm and BCG spondylitis. Accurate diagnosis of BCG spondylitis is important because it is an iatrogenic disease, and its treatment is different from usual tuberculous spondylitis. However, distinguishing BCG spondylitis from usual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…Osteitis is rare secondary to BCG immunization, occurring in less than 37 per 100,000 cases [ 56 ]. Updated to 2018, only 23 cases of tuberculous spondylitis or vertebral osteomyelitis following intravesical BCG were reported in the English literature [ 57 ]. All these patients were male, with a mean age of 73.2 (35-94) years and with a median interval of 1.3 years (0.5 months-12 years) between BCG instillation and the onset of spondylitis.…”
Section: Systemic Complicationsmentioning
confidence: 99%
“…Osteitis is rare secondary to BCG immunization, occurring in less than 37 per 100,000 cases [ 56 ]. Updated to 2018, only 23 cases of tuberculous spondylitis or vertebral osteomyelitis following intravesical BCG were reported in the English literature [ 57 ]. All these patients were male, with a mean age of 73.2 (35-94) years and with a median interval of 1.3 years (0.5 months-12 years) between BCG instillation and the onset of spondylitis.…”
Section: Systemic Complicationsmentioning
confidence: 99%
“…A psoas muscle abscess has been stated in the absence of vertebral involvement. In the literature up to 2018, only 23 cases of tuberculous spondylitis/vertebral osteomyelitis following intravesical BCG were reported [41]. Aljada et al [37] reported a case of Pott's disease after BCG instillation.…”
Section: Discussionmentioning
confidence: 99%
“…Intrarenal BCG is effective in the treatment of upper urinary tract CIS in a long-term follow-up 1. Although BCG therapy is the gold standard of care for high-risk patients intolerant to resection, it can cause rare but serious complications, including sepsis, miliary tuberculosis and spondylitis 2…”
mentioning
confidence: 99%
“…The timeframe for BCG spondylitis onset varies considerably (0.5 months–12 years) 2. Leukocyte counts are usually normal, and CRP levels are lower than those seen in pyogenic vertebral infections.…”
mentioning
confidence: 99%
See 1 more Smart Citation